Investigation of wax deposit 'sloughing' from paraffinic mixtures in pipe flow. (23rd August 2017) - Sinha, Chandni; Mehrotra, Anil K.
Abstract: Deposit 'sloughing' from 'waxy' crude oils has been described in the literature as a possible mechanism, leading to partial or complete dislodging of the deposit from the pipe wall due to changes in flow parameters. A bench‐scale flow loop apparatus was used to investigate 'sloughing' with prepared single‐phase 'waxy' mixtures of a multicomponent paraffinic wax dissolved in a multicomponent solvent. Experiments were performed to study the changes in the deposit‐layer thickness due to step increments in the 'waxy' mixture flow rate, the mixture temperature, and the coolant temperature. It was observed that the deposit‐layer thickness decreased with an increase in each of the three parameters; however, a complete or sudden dislodging of the deposit‐layer did not occur in any of the experiments. A steady‐state heat‐transfer model was used to predict the variation in the deposit mass or thickness due to changes in the selected parameters. In each case, the step‐wise decrease in the deposit thickness, as observed experimentally, was predicted to be caused by changes in the thermal resistance and/or thermal driving force.